Automatic measuring system for head-related transfer function measurement - PRUCHNICKI, Piotr; PLASKOTA, Przemysław (Archives of Acoustics, 2008)
In this paper the Head Related Transfer Function (HRTF) Automatic Measurement Equipment is presented. The system allows to measure HRTF with high spatial resolution within a considerably short time. The system employs many switched sound sources and a rotary chair. HRTF describes a transfer function of the human head and pinna and is unique for each human. Individual measurement of HRTF is necessary for applications where precise simulation of sound source localization is essential. An accurate determination of HRTF requires the position of sound source to be changed in the space surrounding test participants. It necessitates hundreds of measurements with high spatial resolution. The procedure becomes very time consuming and tiring for the participants.